THE RELATIONSHIP BETWEEN DEBT AND TOBACCO EXCISE TAX INCREASES WITH CIGARETTE COMPANY STOCK PRICES - Aini, Yulis Nurul; Djajanto, Ludfi; Utami, Rachma Bhakti; Dja'far, Veri Hardinansyah; Fiernaningsih, Nilawati; Zubaidi, Zubaidi (Jurnal Apresiasi Ekonomi, 2025)
The purpose of this research is to determine the relationship between debt policy and tobacco excise tax rates with stock prices. Data sources were obtained from data published on the Indonesia Stock Exchange and company websites. This research uses multiple regression analysis tools. The research found that first, the debt policy variable has a positive effect on the stock price of tobacco company Gudang Garam (GGRM), while for Sampoerna Company, the debt decision contributes negatively to the stock price. Second, the excise tax rate variable has a negative impact on tobacco stock prices. Third, debt policy and excise tax rates simultaneously affect tobacco stock prices. The implications of these findings indicate that company managers must carefully design debt policies to create optimal capital structure, as the effects of debt decisions can vary between companies. Government policies related to excise tax rates have a direct impact on stock market performance in the tobacco industry, meaning that investors and stakeholders must consider regulatory dynamics as an important factor in investment decision-making. The results of this research provide evidence that excise tax rate adjustments not only affect state revenues but also affect the stability and valuation of companies related to the tobacco industry in the capital market.